Fractional Differential Equation of LC and LR Electrical Circuit - C. P. Jadhav, Dr. A. A. Navlekar, Dr. Kirtiwant P. Ghadle, Dr. S. L. Dhondge (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The fractional derivative isused to calculate the current and charge at any time t in LC,RC and LR circuits by using Laplace Transform of fractional derivatives.